Outbreak of Endoparasitosis in Free-Range Chickens (Gallus gallus domesticus) in Bahia, Brazil - Santos, Marcos Wilker da Conceição; Conceição, Maurício dos Santos; Santos, Flavia dos; Almeida, Jonatas Campos de; Souto, Erick Platiní Ferreira de; Macêdo, Isabel Luana de; Galiza, Glauco Jose Nogueira de; Frade, Maria Talita Soares (Acta Scientiae Veterinariae, 2021)
Background: Free-range chickens are quite common in Brazil. In this alternative rearing system, the animals are rustic and raised in an extensive system. Free access to “bare soil” results in the increased occurrence of intestinal parasites since larvae and / or eggs of helminths and protozoa oocysts find favorable conditions for their survival and dissemination in the soil. Although the occurrence and importance of parasitic infections in free-range chickens is well known, the objective of this study is to report an outbreak of endoparasites in free-range chickens in the municipality of Barra - BA, in view of bird susceptibility associated with scarcity of studies in western Bahia. Cases: The chickens were kept free, in a bare soil yard in a household at the urban perimeter of the municipality of Barra - BA. Feeding consisted of whole corn grains, thrown directly in the soil. The drinking fountains were dirty and the animals had no history of vaccination or deworming. Symptoms Anorexia, difficulty in eating and in locomotion, presence of seromucous secretion in the oral cavity, emaciation and diarrhea were all observed symptoms. One of the birds presented excessive vocalization, drowsiness and flaccid paralysis of the neck. Necropsy was performed on 3 chickens: 2 females (cases 1 and 2) and 1 male (case 3). Macroscopic analysis revealed the presence of seromucous secretion in the upper respiratory tract of all animals. Specimens of Ascaridia galli were observed in cases 1 and 2, Heterakis gallinarum in cases 2 and 3, Raillietina sp. in cases 2 and 3 and Davainea proglottina in case 1. Microscopically, the animals had an inflammatory infiltrate in the liver and intestines. Some animals presented necrosis of the tracheal epithelial cells, as well as of the epithelial cells present at the apex of the villi. No significant results were found in the coproparasitological exam. Discussion: The diagnosis of endoparasitosis in this outbreak was based on epidemiological, clinical and pathological findings. The prevalence of intestinal parasitosis in free-range chickens is linked to factors such as age, high animal density, absence of sanitary hygienic measures, as well as environmental temperature and humidity. The appearance of injuries in the intestinal mucosa is influenced by characteristics such as parasitic load, concomitant infections, age and the host’s immune status. During necropsy of the birds were found 2 helminths of the Nematoda class (Ascaridia galli and Heterakis gallinarum) and 2 of the Cestoda class (Davainea proglottina and Raillietina sp.). A. galli, seen in 2 cases, is considered low pathogenicity for adult chickens, however young birds are susceptible and can die due to intestinal obstruction and hemorrhages. H. gallinarum is responsible for causing typhlitis, with diarrhea and weight loss, this helminth was found in 2 animals in the present study, however only 1 had changes in the digestive tract. Davainea proglotina and Raillietina spp. might cause, respectively, severe hemorrhagic enteritis and nodule formation in the small intestine mucosa. In Brazil, even though it is notable that intestinal parasitism is one of the key problems in alternative poultry farming, there are few studies that evaluate the presence of endoparasites in chickens raised in alternative production systems, with animals being more frequently exposed to nematodes and cestodes. The multiparasitism observed in this study probably stems from flaws in the rearing system, mainly related to sanitary hygiene management. Therefore, the reduction in the occurrence of these helminths is closely related to the performance of basic prophylactic measures, such as offering good quality food and water in clean containers, separating lots by age, performing sanitary emptiness and deworming. Keywords: livelihood creation, nematode, cestode, multiparasitism, avian pathology. Surto de endoparasitose em galinhas caipiras (Gallus gallus domesticus) na Bahia, Brasil Descritores: criação de subsistência, nematoide, cestoide, multiparasitismo, patologia aviária.